Clinical case of a syndrome of Miller-Fisher in practice of children’s infectious diseases - O. Yu. Leonteva; O. V. Samodova; K. A. Kulikova; T. M. Veselova; L. V. Vepreva (Журнал инфектологии, 2014)
.